Breast Angiosarcoma Metastatic to the Ovary - Frederico F. Souza; Amol Katkar; Annick D. Van den Abbeele; Pamela J. Dipiro (Case Reports in Medicine)
Ovarian masses are common findings in general gynecological practice. Approximately 5%–10% of ovarian malignancies are diagnosed as metastatic tumors. Primary angiosarcoma can arise anywhere in the body and when it arises in the breast, it usually affects women in their 3rd and 4th decades and accounts for one in 1700–2300 cases of primary breast cancer. Although unusual, breast angiosarcomas tend to metastasize hematogenously rather than lymphogenously, have high rates of local recurrence, that often develop metastases soon after treatment, and have a dismal prognosis. We present a case of a solitary ovarian metastasis from angiosarcoma of the breast.